The school-to-prison pipeline: education, discipline and racialized double standards - Heitzeg, Nancy A. (Racism in American institutions, 2016)
School to prison pipeline: education on lockdown -- School to prison pipeline: education, race, and social control -- School to prison pipeline: segregated schools, sociopolitical shifts and education under siege -- School to prison pipeline: the context of social control -- School to prison pipeline and racialized control in the era of color blindness -- School to prison pipeline and the prison industrial complex: profit, race and the prison track -- School to prison pipeline and the medical industrial complex: race and the double standards of diagnosis -- School to prison pipeline: punitive policies and transformative alternatives -- Criminalized education, schoolhouse as jailhouse -- Education not incarceration: ending the school to prison pipeline